WILAYATUL HISBAH & SYARIAT ISLAM DI ACEH: Tinjauan Wewenang dan Legalitas Hukum - Samsul Bahri (Jurisprudensi : Jurnal Ilmu Syariah, Perundangan-Undangan dan Ekonomi Islam, 2017)
Legality in the implementation of a rule or Qanun is very important to avoid actions that violate the law. Aceh in the course of time tried to improve the implementation of sharia law by ratifying several qanuns of sharia. With the increase of those qanuns, certainly it will give some changes to the authority of Wilayatul Hisbah (WH) institution in the supervision and the action against the violation of Islamic Sharia in Aceh, especially after the enactment of Aceh Qanun no. 7 in 2013 on the procedural of Islamic Criminal Law and Aceh Qanun no. 6 in 2014 on Criminal Law. This article tries to describe the development of of the implementation of Islamic law with an account on Wilayatul Hisbah in the record of history till the contemporary situation from the aspects of law sources and it’s authority in the enforcement of Sharia law.